Implementasi Program Bantuan Keuangan Khusus Desa Untuk Pemberdayaan Bum Desa Dari Provinsi Jawa Timur Di Kabupaten Kediri - Wahyudi, Diana Putri (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
The East Java Provincial Government through the Community and Village Empowerment Service has launched the Special Financial Assistance (BKK) Village Program for the Empowerment of Village-Owned Enterprises (BUM Desa), which is in the form of capital participation for the development of business units managed by BUM Desa. In Kediri Regency, there are 6 villages that receive this capital assistance for the development of BUM Desa. This program aims to encourage village economic growth, provide additional capital for the development of BUM Desa, and increase the institutional capacity of BUM Desa. This is done because many BUM Desa in Kediri Regency still lack adequate human resources to manage their business units optimally. This study aims to determine the implementation of the special village financial assistance program for the empowerment of BUM Desa in Kediri Regency. Data collection techniques used in this study include interviews and relevant literature reviews. Through these techniques, this study can identify supporting and inhibiting factors for program implementation. In this study, the theory of Van Meter and Van Horn (1975) was used, which includes six variables, namely standards and targets, resources, characteristics of implementing organizations, inter-organizational communication, implementing attitudes, and the social, economic, and political environment. The results of the study indicate that the implementation of the special village financial assistance program for empowering BUM Desa in Kediri Regency is still not optimal. This is due to the limited human resources owned by BUM Desa to manage business units optimally, as well as the many rules in implementing the program that make BUM Desa administrators feel difficult, especially in terms of administration